Exploring Undergraduate Nursing Students' Perceptions on Clinical Learning Environment in the UAE: A Focus on Perceived Benefits and Challenges - Imad Maalouf PhD, MPH, ME, BSN; Wafaa El Zaatari PhD, ME, BSN (SAGE Publishing, 2024)
Introduction Establishing a supportive clinical environment is paramount for enhancing nursing students' engagement in clinical practice, their clinical proficiencies, and satisfaction. The increase in nursing student enrollment at the Nursing College, driven by the collaborative efforts between Abu Dhabi Health Services Company (SEHA) and universities, has given rise to concerns regarding the quality of education and clinical instruction. These concerns are primarily due to the increased student-to-instructor ratio. Furthermore, the unsupportive clinical settings and learning tensions underscore the need to understand students' learning experiences and address research gaps within the field of clinical learning in the United Arab Emirates (UAE). Objectives The purpose of this study is to investigate the undergraduate nursing students' perceptions of their clinical learning environment, with a focus on perceived benefits and challenges. Methods This study used a cross-sectional survey design. The researchers administered a five-point Likert scale questionnaire, which had been adapted and contextualized, to a convenience sample of 217 third and fourth-year nursing students who willingly participated in this study. Results Despite the presence of positive aspects, such as diverse clinical experiences and strong support from both clinical instructors and peers, several challenges affect the students' clinical learning. These challenges encompass disparate perceptions of supervision among staff nurses, learning tensions related to student academic workload, insufficient clinical supervision, and difficulties in finding assistance when needed. Conclusion There is a clear need to enhance the overall ward learning environment to optimize students' academic motivation and clinical skills. Several measures can be taken to achieve this goal, including incentivizing and reducing the workload of staff nurses, investing in the professional development of clinical instructors, promoting peer interactions and group learning, and adopting a block pattern of education in years three and four for better clinical knowledge assimilation and reduced theoretical workload.